1986
DOI: 10.1111/j.1651-2227.1986.tb10353.x
|View full text |Cite
|
Sign up to set email alerts
|

How Common Is Food Allergy?

Abstract: ABSTRACT. In the absence of accurate epidemiological data, it is recognised that significant food allergy will affect a proportion of the atopic group, which itself comprises about 10% of the childhood population. Some food allergic children will also be found among non‐atopics and many allergic children will lose their allergy as they grow through infancy. Early feeding choices probably have less effect on the occurrence of allergy than was previously thought. Some children may also react adversely but not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…These large differences can be attributed to the use of variable diagnostic criteria such as the number of milk challenges, and the various immunological tests used [8,22,24,25,28]. Variability in patient selection [4,6,10,19,26,28], types of feeding regime [14,22], as well as differences in study design such as retrospective evaluation in some studies [17,22] and prospective in others [10,14] also explain the large variations in reported incidence rates. The first objective of this study was to establish the prevalence of CMPI in an unselected group of newborn infants.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…These large differences can be attributed to the use of variable diagnostic criteria such as the number of milk challenges, and the various immunological tests used [8,22,24,25,28]. Variability in patient selection [4,6,10,19,26,28], types of feeding regime [14,22], as well as differences in study design such as retrospective evaluation in some studies [17,22] and prospective in others [10,14] also explain the large variations in reported incidence rates. The first objective of this study was to establish the prevalence of CMPI in an unselected group of newborn infants.…”
Section: Introductionmentioning
confidence: 92%
“…Abbreviation: CMPI = cow's milk protein intolerance incidence rates of CMPI range from 0.3% to 7.5% [6,10,14,28]. These large differences can be attributed to the use of variable diagnostic criteria such as the number of milk challenges, and the various immunological tests used [8,22,24,25,28].…”
Section: Introductionmentioning
confidence: 99%
“…However, there was considerable variation of progress in leafy vegetables and meat. Meat and other animal protein was introduced rather later than recommended, possibly because of concern by the mother that the early introduction of protein might cause food allergy (Croner et al, 1982;Wood, 1986). It should be noted that leafy vegetables are one of the materials introduced early and recommended as weaning food (American Department of Health, 1986), but because of its fiber it is difficult for many infants and preschool children to accept.…”
Section: Discussionmentioning
confidence: 99%
“…These diseases range from allergic rhinitis (hay fever) to asthma, eczema, insulin-dependent diabetes mellitus and rheumatoid arthritis. As far as food is concerned, there needs to be a distinction between true allergy (where the food causes an unhelpful immune response, and antibodies are raised against the specific allergens in the food), and food intolerance (where the food causes unpleasant symptoms for other reasons) (Wood, 1986).…”
Section: Weaning and The Avoidance Of Allergensmentioning
confidence: 99%